Factors Affecting Customer Satisfaction at J&T Express in Malaysia - Sin, Liem Gai; Leong, Joon Weng; Lee, Shu Jie; Lee, Wei Keat; Lee, Zhi Qing (AIBPM Publisher, 2022)
This J&T Express is a courier company in Southeast Asia that emphasizes customer-oriented service and efficiency. Many shopping platforms such as Lazada, Shopee, Tiktok, and others have chosen J&T Express as one of their logistic partners. This research provides consumers' evaluation of every detail of J&T Express' operations and how the company improves and maintains those evaluations. The research examines how customer satisfaction is influenced by price, convenience, service quality, and safety. We applied SPSS to test hypotheses with a sample size of 150 customers. The online survey was carried out through Google Forms. The findings revealed that customer satisfaction was strongly influenced by service quality, safety, and price when using J&T Express. Keywords: Convenience, Customer Satisfaction, J&T Express, Price, Safety, Service Quality.